Kualitas Hasil Penimbangan Berat Badan Balita oleh Kader Posyandu - T Khairul Fadjri (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2016)
Posyandu is a community center in the effort to health and family planning services the needs of health and improvement of nutritional status of the community. It takes care and an adequate place and Posyandu cadres are really well trained and have knowledge about the procedure of weighing. This study intends to determine the factors associated with quality of infant body weight by a cadre of neighborhood health center in the sub-district of Jeumpa, this research descriptive analytic with cross-sectional study design, the sample is Posyandu cadres in the subdistrict of Jeumpa, Bireuen. Statistical analysis Chi-Square test showed that there was a correlation posyandu cadre of knowledge about the body weight of five years with the quality of their body weight infants with p=0,001, there was a correlation with the quality of training of cadres posyandu weight infants weighing results with p= 0,001, and there is a relationship with a quality education cadre posyandu weight infants weighing results with p=0,005. The conclusion of this study were factors associated with quality of infant body weight by a cadre of neighborhood health center in the District Jeumpa Bireuen is knowledge, training, and education of cadres posyandu. Suggested to the parties, especially PHC Jeumpa in order to further enhance the knowledge, training and determination of equitable educational strata in recruiting cadres posyandu. Keywords: Cadres, posyandu, quality weighing results